TURKEY’S FOREIGN POLICY IN CENTRAL ASIA AND THE CAUCASUS: ECHOES OF THE ARAB SPRING - VARBANETS, Pavel (CENTRAL ASIA AND THE CAUCASUS, 2012)
In recent years, Central Asia and the Caucasus have traditionally been a priority of Turkey’s foreign policy. Since the beginning of the 1990s, Ankara has been pursuing an active campaign aimed at establishing close relations with the Turkic republics in this region. However, despite the loud statements and assorted declarations about the development of friendly relations with fraternal peoples, Turkey has not made any significant progress in this vector (apart from strengthening its relations with Azerbaijan). Furthermore, when the Arab Spring uprisings began at the end of 2010-beginning of 2011, Turkey’s official authorities were accused, both inside and outside the country, of conducting a one-dimensional foreign policy oriented only toward the Arab world. The opposition also joined these accusations, saying that the ruling Justice and Development Party was ignoring the Central Asian vector of foreign policy. So, two questions arise. First, how can the Arab Spring demonstrations have an effect on the development of Turkey’s relations with the Central Asian and Caucasian countries? And second, what will Ankara’s foreign policy be in the region in the next few years? The author primarily focuses on Turkey’s relations with the region’s Turkic republics— Azerbaijan, Kazakhstan, Turkmenistan, Uzbekistan, and Kyrgyzstan; other countries remain beyond the scope of this study.